Efecto de la temperatura sobre la calidad postcosecha del apio criollo - Garcia, A.=700 1 Pacheco Delahaye, E.
(Es, En)
ilus., 17 ref.
Keywords: ARRACACIA XANTHORRHIZA; APIO; CALIDAD; ALMACENAMIENTO; RAICES; VENEZUELA; APIO CRIOLLO; CALIDAD POSTCOSECHA; MANEJO POSTCOSECHA; AGRONOMIA TROPICAL